2019
DOI: 10.1038/s41598-019-50952-0
|View full text |Cite
|
Sign up to set email alerts
|

The capacity of wastewater treatment plants drives bacterial community structure and its assembly

Abstract: Bacterial communities in wastewater treatment plants (WWTPs) affect plant functionality through their role in the removal of pollutants from wastewater. Bacterial communities vary extensively based on plant operating conditions and influent characteristics. The capacity of WWTPs can also affect the bacterial community via variations in the organic or nutrient composition of the influent. Despite the importance considering capacity, the characteristics that control bacterial community assembly are largely unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 45 publications
(64 reference statements)
2
20
0
Order By: Relevance
“…The results of this study suggest that the microbial communities are generally different according to the capacity of WWTPs, without some exceptions, such as the dominance of Mycrobacterium genera between large- and small-scale WWTPs. This is consistent with previous studies [ 10 , 56 , 57 ]. Although there are many reasons, similar fitness levels of the microbial community from the influent wastewater community may fit the bioreactor despite different WWTP scales.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The results of this study suggest that the microbial communities are generally different according to the capacity of WWTPs, without some exceptions, such as the dominance of Mycrobacterium genera between large- and small-scale WWTPs. This is consistent with previous studies [ 10 , 56 , 57 ]. Although there are many reasons, similar fitness levels of the microbial community from the influent wastewater community may fit the bioreactor despite different WWTP scales.…”
Section: Resultssupporting
confidence: 94%
“…However, most previous studies preliminarily focused on the identification of ARGs and ARB during the wastewater treatment process, such as activated sludge and anaerobic digestion processes, not considering the scale and treatment capacity of WWTPs [ 6 , 8 ]. According to a previous study, the capacity of a WWTP can affect the bacterial community via various operation practices, such as influent characteristics, sludge retention time (SRT), hydraulic retention time (HRT), reactor volumes, and physical constraints [ 10 ]. Recent studies have suggested that the bacterial community plays a key role in ARG prevalence and enrichment during the WWTP process [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined "Acidobacteriota" in WWTPs, and only a couple of key populations have been explored in detail. Geothrix is recognized as an abundant lineage in nutrient removal WWTPs in South Korea and Vietnam (Kim et al, 2019), suggesting Geothrix to be metabolically active and growing in the plants. In a study by Saunders et al (2016), an unknown genus from the "Acidobacteriota" order with the placeholder name "Sva0725" was defined as a member of the abundant core genera also suggesting them growing in the plants and influencing carbon turnover.…”
Section: Resultsmentioning
confidence: 99%
“…Most characterized taxa in activated sludge WWTPs across the world are from the phyla Proteobacteria, Actinobacteriota, Bacteroidota, Spirochaetota, and Nitrospirota (Wu et al, 2019), but other less well-described phyla are also observed as abundant. For example, almost nothing is known about the potential roles of abundant "Acidobacteriota" members in the wastewater treatment process and only a few studies have visualized (McIlroy et al, 2015a) or evaluated the abundance of "Acidobacteriota" in situ (Juretschko et al, 2002;McIlroy et al, 2015b;Saunders et al, 2016;Kim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Other families, like the Bacteroidaceae, Desulfobacteraceae, Geobacteraceae, and Methylocystaceae, were more abundant at the surface (Figures 7b and 8b), indicating that they may include some facultative anaerobic species, the abundance of this families can be enhanced by a slight increase in oxygen levels. In addition to oxygen availability, it has been suggested that substrate availability and competitive interactions between microbial populations shape the distribution of the bacterial communities from inlet to outlet in anaerobic treatment units such as up flow anaerobic sludge blanket reactors [90,91].…”
Section: Families Degrading Organic Mattermentioning
confidence: 99%